Caminhantes. Um itinerário filosófico - Paula Ponce de Leão (Classica Digitalia: Ideia, 2019)
This work addresses man's current situation in the world, as compared to other historical periods, focusing on the problematic of life and its multiple crossroads which challenge current Philosophy to find a way in both language and poetry to voice the inexpressible and serve as an pathway of survival. What is sought here is a Philosophy accompanying lifeworld, in line with the phenomenological movement and its hermeneutical conversion. Walkers faces, from a philosophical point of view, the serious issues raised by violence, globalization and modern man's solitude.